The Relationship of Interest to Learning Outcomes in the History Subject in Senior High School - Arjad, Arjad; Farid, Farid (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research aims to determine the relationship between interest and learning outcomes in class X history subjects at senior high school 1 Sindue. Methodology: This type of research is quantitative research. The population in this study was class X students of senior high school 1 Sindue, totaling 140 people, while the sample was 35 people. Data collection techniques use observation techniques, questionnaires and test questions. The data analysis techniques used are descriptive analysis and inferential analysis. Main Findings: Product moment calculation results obtained a correlation coefficient (r) of 0.781 or 7.177%. To find out whether the value obtained through the correlation coefficient has meaning or not, hypothesis testing is carried out. Based on the t test, it is known that tcount is greater than t table or t count 7.177 > ttable 1.692, so the correlation that occurs has meaning ( rejected and accepted). So in this research, there is a relationship between interest and learning outcomes in class X history subjects at senior high school 1 Sindue. Novelty/Originality of this study: This research creates new knowledge by revealing the relationship between interest and learning outcomes in history subjects at senior high school 1 Sindue, contributing to the understanding of the factors that influence student academic achievement. This can provide readers with insight into the extent to which students' interests can influence their learning outcomes in history subjects.